2020
DOI: 10.1159/000506813
|View full text |Cite
|
Sign up to set email alerts
|

A Single Motivational Lecture Can Promote Modest Weight Loss: A Randomized Controlled Trial

Abstract: Background: Obesity is a public health problem worldwide. To widely disseminate weightloss interventions across the target population, a cost-effective approach is needed. Objective: We aimed to test whether a single motivational lecture could promote weight loss. Methods: Our study was a 3-month randomized controlled trial, and we recruited participants via local newspaper advertisements in 3 cities in Ibaraki Prefecture, Japan, and randomly assigned them to a control group (no intervention) and an interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This may be because the control group in our study demonstrated a certain weight loss effect after 1 lecture and a few text messages even without using the app. A study has shown that a single motivational lecture can promote moderate weight loss in the short term [ 32 ]. Moreover, our study and the previous study [ 32 ] consisted of populations that were motivated to lose weight, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because the control group in our study demonstrated a certain weight loss effect after 1 lecture and a few text messages even without using the app. A study has shown that a single motivational lecture can promote moderate weight loss in the short term [ 32 ]. Moreover, our study and the previous study [ 32 ] consisted of populations that were motivated to lose weight, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that a single motivational lecture can promote moderate weight loss in the short term [ 32 ]. Moreover, our study and the previous study [ 32 ] consisted of populations that were motivated to lose weight, which may have influenced the results. In addition, many intervention studies using mobile apps included several support tools in the apps, such as texts, emails, internet, interactive chatbots, and voice agents.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions also help prevent disease exacerbation in such individuals as secondary prevention measures. [1][2][3][4][5] In Japan, specific health check-ups and health guidance became institutionalized in 2008 as universal measures for secondary prevention. 1,6 Thus, all residents with public health insurance aged 40-74 years are eligible for specific health check-ups.…”
Section: Introductionmentioning
confidence: 99%